Correlation between Gut Microbiome and Disease Severity in Patients with Acute Pancreatitis: A Prospective Cross-sectional Study - HAN Ziying; SONG Kai; FAN Zhengyang; SONG Xiao; HU Xiaomin; WU Dong (Xiehe Yixue Zazhi, 2022)
Objective  To investigate the gut microbiome composition and changes and its association with disease severity in patients with acute pancreatitis (AP).  Methods  This study was a prospective cross-sectional analysis. The subjects of the study were AP patients in Peking Union Medical College Hospital from June 2018 to January 2022 and healthy volunteers. The clinical data and stool samples of the two groups were collected, the 16S rRNA of the gut microbiome was DNA sequenced, and bioinformatic analysis was performed. The differences in gut microbiome between the two groups were compared, and the correlation between the intestinal flora and the severity of AP was analyzed by receiver operating characteristic(ROC) curve.  Results  A total of 60 AP patients and 20 healthy volunteers were enrolled. Among the AP patients, 20 were mild AP, 20 were moderately severe AP, and 20 were severe AP. During hospitalization, 22 cases were transferred to ICU, while 38 cases were not. In α diversity analysis, the Shannon index of AP patients was significant decreased compared to healthy volunteers (P < 0.05). β diversity of the two groups was significantly different. At the phylum, family, genus and species levels, there were also significant differences in the microbiome composition between the two groups. Linear discriminant analysis effect size analysis revealed that g_Escherichia-Shigella, g_Enterococcus, and f_Enterococcaceae were dominant in AP patients while g_Blautia, and g_Bifidobacterium were dominant in healthy volunteers. Function analysis found that multiple amino acid biosynthesis pathways were blocked in gut microbiome of AP patients, and potential pathogenicity and migration ability of gut microbiome increased significantly. In subgroup analysis, g_Enterococcus was increased and g_Bacteroidaceae was decreased in ICU patients compared to non-ICU patients. Based on the probability of disease index, the ROC curve showed that the area under the curve for identifying AP patients and AP patients transferred to ICU were 0.996 and 0.743.  Conclusions  The pathogenic bacteria increased and the beneficial bacteria decreased in the gut microbiome of AP patients. Changes in gut microbiota are related to the severity of AP disease and therefore have the potential to be used as novel biomarkers for AP.